PENDUGAAN DEFISIT AIR TANAMAN JARAK (RICINUS COMMUNIS L) BERDASARKAN MODEL SIMULASI DINAMIKA AIR TANAH(PREDICTION WATER DEFICIT OF CASTOR OIL (RICINUS COMMUNIS L) WITH DYNAMIC SOIL-WATER MODEL SIMULATION) - F. Djufri; A. Yanto; . Handoko; Yonny Koesmaryono (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2005)
Construction dynamic model soil – water that describes relationships between crop growth and development and environmental factors (weather and soil) can be further developed to be employed as a decision support tool . The objectives of the research : (1) to know interaction of factor weather , soil, castor oil crop, (2) construction dynamic model soil – water , (3) monitoring water deficit factor at level of water irrigation. The research consisted field observation and construction model. The experimental results were used to determine quantitative relationships to obtain model parameters, calibration, and validation. This research was conducted in field experimental station of Balitpa Sukamandi, and it was arranged in split plot design with three replications. Two variety of castor oil as main plot design were : (1) ASB 81, (2) ASB 60. Three levels of water irrigation as sub plot design were : (1) No water irrigation, (2) ½ ETp, (3) 1 ETp. Field measurements included weather variables, soil, and crop. The t-test does not indicate significant difference between observed and predicted soil water content. The model is valid and reasonably well for predicting soil water content as long as castor growth . The dynamic model soil-water can be employed as a decision support tool in the management of castor oil plantations in Indonesia.